This Contentious Storm: An Ecocritical and Performance History of King Lear - Hamilton, Jennifer Mae (Environmental Cultures, 2017)
This book is available as open access through the Bloomsbury Open Access programme and is available on www.bloomsburycollections.com. From providential apocalypticism to climate change, this ground-breaking ecocritical study traces the performance history of the storm scene in King Lear to explore our shifting, fraught and deeply ideological relationship with stormy weather across time. This Contentious Storm offers a new ecocritical reading of Shakespeare's classic play, illustrating how the storm has been read as a sign of the providential, cosmological, meteorological, psychological, neurological, emotional, political, sublime, maternal, feminine, heroic and chaotic at different points in history. The big ecocritical history charted here reveals the unstable significance of the weather and mobilises details of the play's dramatic narrative to figure the weather as a force within self, society and planet.